Closed-loop obstruction due to internal hernia: An atypical clinical presentation of acute abdomen — A case report - Varsha Chinta; Sunil M Krishna; Vivek Ramesh Udupi (International Journal of Abdominal Wall and Hernia Surgery)
Internal hernia is the protrusion of a viscus through a normal or abnormal peritoneal or mesenteric aperture within the confines of the peritoneal cavity. They can be congenital or acquired after abdominal surgery. We report a case of a 58-year-old woman who presented with complaints of abdominal pain and nonbilious vomiting for 2 days. She underwent an abdominal hysterectomy 15 years ago. After baseline blood investigations and imaging, a diagnosis of subacute intestinal obstruction was made. As she clinically worsened over 24 h, CT imaging was done, which suggested acute small bowel obstruction secondary to adhesions. Surgery revealed herniation with incarceration of distal ileal loops through a defect in the sigmoid mesocolon. Bowel resection was done, and the defect was closed. The clinical presentation of internal hernias, especially transmesosigmoid hernia, is nonspecific, and they rapidly progress to bowel ischemia. Early intervention and surgical correction are prudent for good clinical outcomes.